Urgensi Layanan Informasi Berbasis Digital pada Pandemi Covid-19: Sebuah Tinjauan Kepustakaan Sistematis - Muhammad Ibnu Majah; Elva Oktafiani; Muhammad Thufeil Imtinan (Universitas Mataram, 2022)
Many published scientific studies from January-August 2021 discuss the COVID-19 pandemic and its relationship to digital technology. This publication demonstrates the ease of digital technology in helping the Indonesian people to deal with the COVID-19 pandemic. But in reality, the increase in the number of patients until the government implements the PPKM Mandiri policy (July-August 2021) continues to increase. The research method using a systematic literature review can find out what happened in Indonesia during the COVID-19 pandemic through published articles. The search for scientific literature was carried out using Mendeley References through the keywords digital technology and covid-19. The data obtained regarding the issue of digital technology and covid-19 and research in the territory of Indonesia obtained 80 articles. The data were analyzed and concluded that the largest research on online education is due to restrictions on face-to-face learning. Increasing the economy by strengthening digital technology to bring together buyers and sellers in tackling the decline in purchasing power and many transactions are written. However, technology to cope with the increasing number of patients and deaths due to the COVID-19 pandemic is not sufficiently considered in published scientific articles, so the public is not given sufficient knowledge about COVID-19 through digital technology. These results can provide input on digital technology policies that the Government of Indonesia should carry out to help reduce the number of patients and deaths due to the COVID-19 pandemic.